Clinical factors related to undescended testis in infants with gastroschisis. Issue 1 (26th March 2022) - Umeda, Satoshi; Takayama, Keita; Takase, Koki; Kim, Kiyokazu; Yamamichi, Taku; Tayama, Ai; Usui, Noriaki
Abstract: Background: Recent studies have reported the high incidence of undescended testis (UDT) in patients with gastroschisis. Although various mechanical, hormonal, and genetic theories have been postulated to describe testicular descent, the mechanism contributing to this condition remains controversial. We aimed to investigate the incidence and risk factors of UDT in infants with gastroschisis. Methods: Male neonates who underwent surgery for gastroschisis between January 1982 and December 2019 were enrolled. Data were analyzed regarding the prevalence of UDT, including spontaneous testicular descent and the necessity of orchidopexy. Patients were grouped into those with or without UDT to identify the risk factors for UDT. Results: Among 38 patients with gastroschisis, six (15.8%) developed UDT. There were no significant differences in gestational age or birthweight between patients with and without UDT. The patients with UDT had a significantly larger defect size than those without UDT ( P  = 0.037). In addition, the timing of abdominal closure was significantly later in patients with UDT than in those without UDT ( P  = 0.004). None of the patients with UDT exhibited spontaneous testicular descent requiring subsequent orchidopexy. Conclusions: Patients with gastroschisis had a high prevalence of UDT. In gastroschisis, the incidence of UDT was related to the defect size and the timing of abdominal wall closure, indicating that an insufficient increase in intra‐abdominal pressure during the fetal period may affect the development of UDT.